Risk of SARS-CoV-2 infection among front-line healthcare workers in Northeast Brazil: a respondent-driven sampling approach - Thalia Velho Barreto de Araújo; Demócrito de Barros Miranda-Filho; Ricardo Arraes de Alencar Ximenes; Ulisses Ramos Montarroyos; Celina Maria Turchi Martelli; Maria de Fátima Pessoa Militão de Albuquerque; Wayner Vieira de Souza; Cresio Romeu Pereira; Cynthia Braga; Celia Landmann Szwarcwald; Paulo Roberto Borges de Souza-Junior; Morgana Nascimento Xavier; et al. (BMJ Open)
Objectives We assessed the prevalence of SARS-CoV-2 infection, personal protective equipment (PPE) shortages and occurrence of biological accidents among front-line healthcare workers (HCW).Design, setting and participants Using respondent-driven sampling, the study recruited distinct categories of HCW attending suspected or confirmed patients with COVID-19 from May 2020 to February 2021, in the Recife metropolitan area, Northeast Brazil.Outcome measures The criterion to assess SARS-CoV-2 infection among HCW was a positive self-reported PCR test.Results We analysed 1525 HCW: 527 physicians, 471 registered nurses, 263 nursing assistants and 264 physical therapists. Women predominated in all categories (81.1%; 95% CI: 77.8% to 84.1%). Nurses were older with more comorbidities (hypertension and overweight/obesity) than the other staff. The overall prevalence of SARS-CoV-2 infection was 61.8% (95% CI: 55.7% to 67.5%) after adjustment for the cluster random effect, weighted by network, and the reference population size. Risk factors for a positive RT-PCR test were being a nursing assistant (OR adjusted: 2.56; 95% CI: 1.42 to 4.61), not always using all recommended PPE while assisting patients with COVID-19 (OR adj: 2.15; 95% CI: 1.02 to 4.53) and reporting a splash of biological fluid/respiratory secretion in the eyes (OR adj: 3.37; 95% CI: 1.10 to 10.34).Conclusions This study shows the high frequency of SARS-CoV2 infection among HCW presumably due to workplace exposures. In our setting, nursing assistant comprised the most vulnerable category. Our findings highlight the need for improving healthcare facility environments, specific training and supervision to cope with public health emergencies.